O processo da leitura e da escrita dos alunos de fundamental maior: um estudo de caso em uma turma de 8° ano de uma escola estadual no município de Abaetetuba-PA - NEGRÃO, Michelle da Costa (2024)
The work that has as theme: THE PROCESS OF READING AND WRITING OF THE FUNDAMENTAL MAJOR STUDENTS: A case study on a 8 year class in a state school in the city of Abaetetuba Pará is based on the line of thought of theoretical underpinning writing a text and reflex actions of the construction of a text being:. Bentes (2001; Smith and Teberosky (1999; Smith (2001; Vygotsky (1999; Bezerra (2012 Thus, in order to write about it with a view to analyzing the theoretical principles that support the textual language being based reflect on the understanding about the framework of idea and sequential as a network of relationships that constitute the text Guided that goal appeared relevant contesting the focus of interest linked to that work as:. what the text of the concept? What is the conceptual approach on textual language? What is the relationship between theory and practice and the difference between reference and sequential? Based on the assumption these questions we decided to make lined literature the practice of field research. Based on theoretical arguments after take all the stages of the work we conclude that the text has components that need to be analyzed and valued as dialogue which has its own theoretical dimensions that underlie and puts in evidence to be explored in the field of language skills, according a textual structure to be developed with clear and cohesive discursive arguments.